2016
DOI: 10.3390/brainsci6030027
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Temporal Asymmetry Associated with Distinct ON and OFF Responses to Time-Varying Sounds with Rising versus Falling Intensity: A Magnetoencephalography Study

Abstract: This magnetoencephalography (MEG) study investigated evoked ON and OFF responses to ramped and damped sounds in normal-hearing human adults. Two pairs of stimuli that differed in spectral complexity were used in a passive listening task; each pair contained identical acoustical properties except for the intensity envelope. Behavioral duration judgment was conducted in separate sessions, which replicated the perceptual bias in favour of the ramped sounds and the effect of spectral complexity on perceived durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…Given that multiple analysis techniques (for example, waveform analysis, source localization, time-frequency analysis) can be applied to the same neurophysiological data in cognitive neuroscience research [54,57,58,59], a cautionary note against the convenient use of the simple Pearson correlation test is necessary when selecting and applying statistical models to interpret brain-behavior correlations (e.g., biomarkers of various diseases and disorders) or correlations among the various brain measures with prior distributions and covariance structure for repeated measures. …”
Section: Discussionmentioning
confidence: 99%
“…Given that multiple analysis techniques (for example, waveform analysis, source localization, time-frequency analysis) can be applied to the same neurophysiological data in cognitive neuroscience research [54,57,58,59], a cautionary note against the convenient use of the simple Pearson correlation test is necessary when selecting and applying statistical models to interpret brain-behavior correlations (e.g., biomarkers of various diseases and disorders) or correlations among the various brain measures with prior distributions and covariance structure for repeated measures. …”
Section: Discussionmentioning
confidence: 99%
“…In these cases, as stated before, it is difficult to disentangle neural oscillations from the spectral content of typical evoked potentials. For instance, AEPs or inter-trial phase locking lasting only one or two cycles were possibly misinterpreted as "alpha-beta" activity (Fritz et al, 2010) or "theta" activity (Musacchia et al, 2017;Zhang et al, 2016). More importantly, it questions the accuracy of the conclusions based on very few cycles of oscillations.…”
Section: Short or Broadband Oscillations Are Ambiguousmentioning
confidence: 99%
“…As stated above, the auditory N1 is a prominent cortical electroencephalographic response to both the onset (On-response; On-N1) and offset (Off-response; Off-N1) of an auditory stimulus (Zhang et al, 2016 ). An auditory N1 can also be elicited by infrequent changes in pitch or timbre of a continuous complex tone (Vaz Pato and Jones, 1999 ; Change-N1).…”
Section: The Pu Model: Tinnitus As An Error Of Sound Change Integratimentioning
confidence: 99%
“…The model further postulates that the auditory cortex recognizes sound inputs by comparing it to the input of the previous instant, and thus acts as a detector of input changes. In this model, the auditory N1, a prominent electromagnetic response of the auditory cortex that is elicited ~100 ms after the onset and offset of a discrete tone or after an alteration of a continuous tone (Zhang et al, 2016 ), serves as a marker of this change detection process within auditory cortex. Indeed, recent studies have revealed that the auditory N1 detects change by comparing the information of a preceding stimulus with that of a subsequent stimulus (Inui et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%